Multichannel marketing - Arikan, Akin (Wiley Pub, 2008)
Includes index; With great opportunity come great challenges -- The web analyst tackles multichannel metrics online -- The offline marketer's bag of tricks -- The direct marketer digs into multichannel analytics -- The brand marketer's take on multichannel analytics -- Measure lift between online and offline -- Measure 1:1 interactions between online and offline -- Measure multi-touch conversions -- Attract and acquire -- Engage and convert -- Grow lifetime value; Quỹ Châu Á